Sociopolitical Context of Spain and Mexico: Parallels and Contrasts within the Framework of the Mexican Constituent Process of 1824 - Fernández Molina, María Victoria (Revista Internacional & Comparada de Derechos Humanos, 2024)
The analysis presented in this text examines, using a historical-comparative methodology, how the sociopolitical realities of Spain and Mexico between 1812 and 1824 influenced the creation of their constitutional texts. It studies the convergence of liberal principles and the specific adaptations required by each context, highlighting the influence of the 1812 Constitution of Cadiz on Mexico’s 1824 Constitution. Additionally, it reviews the impact of insurgent documents, such as López Rayón’s Elementos Constitucionales and Morelos’s Sentimientos de la Nación, on the construction of the Mexican constitutional framework. Finally, this article addresses the tensions between centralism and federalism, as well as the role of these constitutions in the quest for an autonomous and cohesive national identity.